The Role of HLA-G in Tumor Escape: Manipulating the Phenotype and Function of Immune Cells - Liu, Lu; Wang, Lijun; Zhao, Lihong; He, Chen; Wang, Ganlu (Frontiers in Oncology, 2020)
HLA-G is a non-classical MHC I molecule, and under physiological conditions, its expression is strictly restricted to the maternal-fetal interface and immune-privileged organs where HLA-G is expected to contribute to establishment and maintenance of immune tolerance. However, the expression of HLA-G has been found in various types of tumors and the level of its expression correlates with high grade and poor prognosis, raising the possibility that it may play a negative role in tumor immunity. ILT2 and ILT4, present on a broad of immune cells, have been identified as the main receptors engaging HLA-G, and their interactions have been found to allow the conversion of effectors like NK cells and T cells to anergic or unresponsive state, activated DCs to tolerogenic state, and drive the differentiation of T cells towards suppressive phenotype. Therefore, tumors can employ HLA-G to modulate the phenotype and function of immune cells, allowing them to escape immune attack. In this review, we discuss the mechanism underlying HLA-G expression and function, its role played in each step of the tumor-immunity cycle, as well as the potential to target it for therapeutic benefit.